2012
DOI: 10.1186/gb-2012-13-10-r100
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation in discrete developmental stages of the parasitic nematode Trichinella spiralis

Abstract: BackgroundDNA methylation plays an essential role in regulating gene expression under a variety of conditions and it has therefore been hypothesized to underlie the transitions between life cycle stages in parasitic nematodes. So far, however, 5'-cytosine methylation has not been detected during any developmental stage of the nematode Caenorhabditis elegans. Given the new availability of high-resolution methylation detection methods, an investigation of life cycle methylation in a parasitic nematode can now be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 41 publications
8
89
0
Order By: Relevance
“…DNMT activity was measured using the DNMT Activity/Inhibition Assay Ultra kit (Epigentek), as described previously (30,31). Briefly, 5-g nuclear extracts for each assay were used as the start material, and the procedure was according to the manufacturer's instructions.…”
Section: Rnamentioning
confidence: 99%
“…DNMT activity was measured using the DNMT Activity/Inhibition Assay Ultra kit (Epigentek), as described previously (30,31). Briefly, 5-g nuclear extracts for each assay were used as the start material, and the procedure was according to the manufacturer's instructions.…”
Section: Rnamentioning
confidence: 99%
“…Furthermore, MeDIP-qPCR analysis revealed that a small amount of methylated DNA might be present in different developmental stages of D. melanogaster (Table 3). The presence of mosaic DNA methylation patterns has been described in different developmental stages of invertebrates 5,[40][41][42][43][44] . DNA methylation increased drastically during developmental stages, and adults exhibited the highest observed DNA methylation level in Trichinella spiralis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mosaic DNA methylation patterns has been described in different developmental stages of invertebrates 5,[40][41][42][43][44] . DNA methylation increased drastically during developmental stages, and adults exhibited the highest observed DNA methylation level in Trichinella spiralis 43 . It has been demonstrated that DNMT1a is essential during early embryogenesis of Nasonia vitripennis and lowering of maternal DNMT1a mRNA resulted in embryonic lethality during the onset of gastrulation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the methylation ascertainment method applied by Lister et al [9], which is widely used in the methylation analysis software such as Bismark [22] and Bisulfighter [23], has been employed to determine the methylcytosines from BS-seq data [5], [24] and has been shown to have a much lower false positive rate than the simple filtering method [25], [26]. We termed the method as “Lister” hereafter.…”
Section: Introductionmentioning
confidence: 99%